Modifications of a conserved regulatory network involving INDEHISCENT controls multiple aspects of reproductive tissue development in Arabidopsis. Issue 1 (5th November 2012) - Kay, P.; Groszmann, M.; Ross, J. J.; Parish, R. W.; Swain, S. M.
Summary: Disrupting pollen tube growth and fertilization in Arabidopsis plants leads to reduced seed set and silique size, providing a powerful genetic system with which to identify genes with important roles in plant fertility. A transgenic Arabidopsis line with reduced pollen tube growth, seed set and silique growth was used as the progenitor in a genetic screen to isolate suppressors with increased seed set and silique size. This screen generated a new allele of INDEHISCENT ( IND ), a gene originally identified by its role in valve margin development and silique dehiscence (pod shatter). IND forms part of a regulatory network that involves several other transcriptional regulators and involves the plant hormones GA and auxin. Using GA and auxin mutants that alter various aspects of reproductive development, we have identified novel roles for IND, its paralogue HECATE3, and the MADS box proteins SHATTERPROOF1/2 in flower and fruit development. These results suggest that modified forms of the regulatory network originally described for the Arabidopsis valve margin, which include these genes and/or their recently evolved paralogs, function in multiple components of GA/auxin‐regulated reproductive development.